REMOVAL OF ARSENIC FROM FRESH WATER USING SUPERPARAMAGNETIC IRON OXIDE NANOPARTICLES SUPPORTED ON SULPHONATED SUGARCANE BAGASSE (Journal of Medical & Health Sciences Review, 2025)
To synthesized superparamagnetic iron Oxide nanoparticles (SPIONS) by using pomegranate pulp extract. Activated carbon was made from sugarcane bagasse using a chemical impregnation process and then superparamagnetic iron oxide nanoparticle supported was on it. By using UV-visible spectroscopy, SEM, XRD and FTIR, the characterization of synthesized  activated carbon (AC), SPION and Modified activated carbon (AC/SPIONs) were performed. According to the pictures of SEM, The synthesised  Nanoparticles were spherical shape, more dispersed and it average ranges in size from 1nm-100nm. The functional groups and their physical interaction with SPIONs were showed in the FT-IR data. The XRD pattern demonstrated that the produced nanoparticles were crystalline. The majority of SPIONs were found to be attached to activated carbon's surface. The atomic absorption spectroscopy was used to analyze the activated carbon for adsorption of arsenic. The outcomes demonstrated that the arsenic ions adsorbed on the synthetic modified activated carbon best matched the Freundlich isotherm model, which predicted a heterogeneous distribution of active site over synthetic adsorbent and Physical adsorption. The Fruendlich constant (n), which indicates effective arsenic ion adsorption, was found to be greater than unity. Synthesised Modified activated carbon demonstrated significant adsorption and can be used for water purification.